The Effect of Hypnotherapy on Work Stress Reduction Among Employees in a Private Company in West Jakarta, Indonesia - Bambang Adhy Prasakti; Nur Asniati Djaali; Titi Indriyati (Jurnal Ilmiah Kesehatan, 2026)
High work stress levels among employees of private companies in West Jakarta negatively impact psychological well-being and individual performance. An effective intervention approach is needed to address this issue, one of which is hypnotherapy. This study aimed to analyze the effect of hypnotherapy on reducing work stress among employees of private companies in West Jakarta. This study used a quasi-experimental design with a pretest-posttest control group design. A sample of 34 respondents was divided into an intervention group (n=16) and a control group (n=18). The research instrument was the Workplace Stress Scale (WSS) questionnaire. The intervention group received hypnotherapy sessions, while the control group did not. Data were analyzed statistically using the Paired t-test and Independent sample t-test, supplemented by thematic qualitative analysis. There was a significantly greater reduction in work stress scores in the intervention group (Mean before=38.25, SD=1.57; Mean after=13.38, SD=2.70; Mean difference=24.87; p<0.001) compared to the control group (Mean difference=3.61; p<0.001). The difference in stress levels between the two groups post-intervention was also significant (p=0.000). Qualitative analysis revealed two main themes: reduction of work stress and improvement of individual performance, reinforced by positive career development changes in the intervention group. Confounding factors such as age, gender, employment status, and job type also influenced the results. Hypnotherapy is proven to be significantly effective in reducing employee work stress. Therefore, it is recommended that companies consider hypnotherapy as an intervention program in organizational stress management. For future research, it is advised to control for confounding factors and explore the long-term impacts of hypnotherapy intervention.